2023
DOI: 10.1186/s40545-023-00555-y
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, practices and perceptions of community pharmacists towards antimicrobial resistance and antimicrobial stewardship in Libya: a cross-sectional study

Abstract: Background Community pharmacists play a vital role in promoting appropriate use of antibiotics in the community. This study evaluated the practices and perceptions of community pharmacists towards antibiotic use, antibiotic resistance, and antimicrobial stewardship in Libya. Methods A cross-sectional study was conducted among community pharmacists in Libya using a 47-item validated, pre-tested online questionnaire. Data was collected from December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Almost similar results were reported from Black Lion Hospital with a slightly higher magnitude, where 82.4 % believed that ASP improves the quality of patient care, ASP reduces overall antibiotic consumption and can result in cost savings (76.9 %), ASP reduces the duration of hospital stay and associated costs (73.5 %), and ASP reduces the problem of AMR (82.9 %) [ 44 ]. In Libya, pharmacy professionals believed that ASP reduces the rate of AMR (70.2 %), reduces inappropriate use of antibiotics in the community (68.4 %), participation in ASP activities will boost public confidence in community pharmacy services (79 %), community pharmacists’ participation in the ASP will promote (73.7 %) and ASP activities are important in the hospital setting but are not important in the community setting (16.7 %) [ 78 ]. This assures that reducing AMR is a public health priority [ 58 ], and the implementation of ASP reduces inappropriate antibiotic use and AMR in hospital settings, in the community and private health facilities as well [ 4 , 51 , [78] , [79] , [80] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost similar results were reported from Black Lion Hospital with a slightly higher magnitude, where 82.4 % believed that ASP improves the quality of patient care, ASP reduces overall antibiotic consumption and can result in cost savings (76.9 %), ASP reduces the duration of hospital stay and associated costs (73.5 %), and ASP reduces the problem of AMR (82.9 %) [ 44 ]. In Libya, pharmacy professionals believed that ASP reduces the rate of AMR (70.2 %), reduces inappropriate use of antibiotics in the community (68.4 %), participation in ASP activities will boost public confidence in community pharmacy services (79 %), community pharmacists’ participation in the ASP will promote (73.7 %) and ASP activities are important in the hospital setting but are not important in the community setting (16.7 %) [ 78 ]. This assures that reducing AMR is a public health priority [ 58 ], and the implementation of ASP reduces inappropriate antibiotic use and AMR in hospital settings, in the community and private health facilities as well [ 4 , 51 , [78] , [79] , [80] ].…”
Section: Discussionmentioning
confidence: 99%
“…In Libya, pharmacy professionals believed that ASP reduces the rate of AMR (70.2 %), reduces inappropriate use of antibiotics in the community (68.4 %), participation in ASP activities will boost public confidence in community pharmacy services (79 %), community pharmacists’ participation in the ASP will promote (73.7 %) and ASP activities are important in the hospital setting but are not important in the community setting (16.7 %) [ 78 ]. This assures that reducing AMR is a public health priority [ 58 ], and the implementation of ASP reduces inappropriate antibiotic use and AMR in hospital settings, in the community and private health facilities as well [ 4 , 51 , [78] , [79] , [80] ].…”
Section: Discussionmentioning
confidence: 99%
“…31 A recent survey conducted in Libya presented a moderate perception of AMR among community pharmacists. 38 This disparity is attributed to varying experiential learning exposure and antibiotic knowledge levels among university students.…”
Section: Perception Toward Antimicrobial Resistancementioning
confidence: 99%
“…Significant evidence has suggested that the knowledge and attitudes of pharmacy professionals and other healthcare workers (HCWs) can play a key role in managing the growing threat of AMR [35] [36] [37] [38]. This is because pharmacy professionals that have good knowledge and positive attitudes towards AMU and AMR usually promote good dispensing practices and rational use of antibiotics [39] [40] [41]. The occupation of pharmacy professionals is increasingly becoming patient-centered thereby making pharmacy professionals the most accessible HCWs [42] [43] [44].…”
Section: Introductionmentioning
confidence: 99%